A race for a better understanding of COVID-19 vaccine non-adopters - Su, Zhaohui; Wen, Jun; Abbas, Jaffar; McDonnell, Dean; Cheshmehzangi, Ali; Li, Xiaoshan; Ahmad, Junaid; Šegalo, Sabina; Maestro, Daniel; Cai, Yuyang (Elsevier Inc., 2020)
In this paper, we aim to underscore the need for a more nuanced understanding of vaccine non-adopters. As the availability of vaccines does not translate into their de facto adoption—a phenomenon that may be more pronounced amid “Operation Warp Speed”—it is important for public health professionals to thoroughly understand their “customers” (i.e., end users of COVID-19 vaccines) to ensure satisfactory vaccination rates and to safeguard society at large.